THE THE INFLUENCE OF THE SUPPLY CHAIN ON THE COMPETITIVE ADVANTAGES OF COMPANIES IN AGRIBUSINESS - Puška, Adis; Nedeljković, Miroslav; Parojčić, Danijela (Economics of Agriculture, 2022)
Changes in the market, caused by globalization, have led to the fact that many companies needed to adapt their operations. In response to these changes, the concept of supply chain was developed to help companies from procurement to sales of products. This paper examines the eﬀects of supply chains on competitiveness using the example of agro-food companies from the Republic of Croatia. The research was conducted through a questionnaire which included 188 agribusiness companies. The responses were systematized and statistically processed using descriptive statistics, correlation analysis and multivariate regression analysis. The results showed that the eﬀects of supply chains play a major role in determining the competitiveness of agro-food companies. Therefore, it is necessary to improve the eﬀects of the supply chain in these companies in order to improve competitiveness and achieve better results of these companies on the market.